22.3k views
0 votes
Evaluate the expression: (–2)2 + (–42) + (18 – 23).

A. –19
B. 19
C. –17
D. 3

User Pranith
by
6.0k points

2 Answers

0 votes

Answer:

-17

Explanation:

Evaluate the expression: (–2)^2 + (–4^2) + (18 – 23) = -17

User Paty
by
5.4k points
3 votes

Answer:

The correct answer is for the given expression is -43.

Explanation:

We are given the following expression and we are supposed to evaluate it:


(-2)^2 + (-42) + (18 - 23)

Solving the terms inside the brackets first, following the order of operations to solve a mathematical expression to get:

= 4 + (-42) + (-5)

Further adding and subtracting the terms to get:

= 4 - 42 - 5

= -38 - 5

= -43

User Justin Helgerson
by
5.2k points